Consecutive β, β′‐Selective C(sp3)−H Silylation of Tertiary Amines with Dihydrosilanes Catalyzed by B(C6F5)3. Issue 15 (3rd March 2021) - Fang, Huaquan; Xie, Kaixue; Kemper, Sebastian; Oestreich, Martin
Abstract: Tris(pentafluorophenyl)borane has been found to catalyze the two‐fold C(sp 3 )−H silylation of various trialkylamine derivatives with dihydrosilanes, furnishing the corresponding 4‐silapiperidines in decent yields. The multi‐step reaction cascade involves amine‐to‐enamine dehydrogenation at two alkyl residues and two electrophilic silylation reactions of those enamines, one inter‐ and one intramolecular. Abstract : Acyclic tertiary amines with alkyl substitution undergo two consecutive C(sp 3 )−H silylation reactions with dihydrosilanes to form 4‐silapiperidines. Bond formation occurs β to the nitrogen atom at two of the alkyl residues. The reaction is catalyzed by the strong boron Lewis acid B(C6 F5 )3 and involves enamine intermediates generated by dehydrogenation.